Late Onset of Antiretroviral Therapy in Adults Living with HIV in an Urban Area in Brazil: Prevalence and Risk Factors - Priscila Ribeiro Guimarães Pacheco; Ana Laura Sene Amâncio Zara; Luiz Carlos Silva e Souza; Marília Dalva Turchi (Journal of Tropical Medicine)
Introduction. Highly active antiretroviral therapy has been available since 1996. Early initiation of antiretroviral therapy (ART) leads to improved therapeutic response and reduced HIV transmission. However, a significant number of people living with HIV (PLHIV) still start treatment late. Objective. This study aimed to analyze characteristics and factors associated with late initiation of ART among HIV-infected treatment-naïve patients. Methods. This cross-sectional study included PLHIV older than 17 years who initiated ART at two public health facilities from 2009 to 2012, in a city located in Midwestern Brazil. Pregnant women were excluded. Data were collected from medical records, antiviral dispensing forms, and the Logistics Control of Medications System (SICLOM) of the Brazilian Ministry of Health. Late initiation of ART was defined as CD4+ cell count < 200 cells/mm3 or presence of AIDS-defining illness. Uni- and multivariate analysis were performed to evaluate associated factors for late ARV using SPSS®, version 21. The significance level was set at p<0.05. Results. 1,141 individuals were included, with a median age of 41 years, and 69.1% were male. The prevalence of late initiation of ART was 55.8% (95%CI: 52.9-58.7). The more common opportunistic infections at ART initiation were pneumocystosis, cerebral toxoplasmosis, tuberculosis, and histoplasmosis. Overall, 38.8% of patients had HIV viral load equal to or greater than 100,000 copies/mL. Late onset of ART was associated with higher mortality. After logistic regression, factors shown to be associated with late initiation of ARV were low education level, sexual orientation, high baseline viral load, place of residence outside metropolitan area, and concomitant infection with hepatitis B virus. Conclusion. These results revealed the need to increase early treatment of HIV infection, focusing especially on groups of people who are more socially vulnerable or have lower self-perceived risk.